Influence of Ce/Zr Ratio on the Synergistic Effect over CuCe1–xZrxOy/ZSM-5 Catalysts for the Self-Sustained Combustion of Carbon Monoxide. Issue 8 (3rd August 2017) - Zhao, Ruozhu; Hao, Qinglan; Bin, Feng; Kang, Running; Dou, Baojuan
ABSTRACT: The self-sustained combustion of CO was studied over a series of CuCe1–x Zrx Oy /ZSM-5 catalysts with different Ce/Zr molar ratios to evaluate the correlation of their structural characteristics with catalytic performance. The obtained results demonstrated that the activity of the cerium-containing catalysts was much higher than that of the CuZr1 /Z, with the activity of CO combustion following the order: CuZr1 /Z < CuCe0.25 Zr0.75 /Z < CuCe0.5 Zr0.5 /Z < CuCe1 /Z < CuCe0.75 Zr0.25 Z. After cerium addition, the cerium-zirconium mixed oxides formed promoted the copper species well dispersed on the catalyst surface. The high activities of cerium-containing catalysts were closely related to the synergetic effects among the copper, cerium, and zirconium species, as the surface copper species provided sites for CO adsorption and the cerium-zirconium mixed oxides promote the activation of oxygen. The activities were probably also attributed to some copper species present as substitutional defects in the ceria lattice, which were more reducible than the copper clusters, minicrystals, and bulk CuO particles. The CuCe0.75 Zr0.25 /Z possessed excellent redox capacity, adsorption/activation properties for O and CO species, and therefore induced a self-sustained combustion of CO at the lowest temperature than that of other CuCe1- x Zr x O y /ZSM-5 catalysts.